Marine Atmospheric Corrosion Behavior of Structural Ferritic Pearlitic and Ferritic Martensitic Weathering Steel [Comportamiento a la Corrosión Atmosférica Marina de Aceros Autopatinables Con Estructura Ferrítico Perlítica y Ferrítico Martensítica] - Sipos-Hrabal, K; Bustos-Castillo, O; Monsalve-Gonzalez, A; Artigas-Abuin, A; Allende-Seco, R (Universidade Federal do Rio de Janeiro, 2015)
The steel industry constantly faces the challenge of developing new and better steels for diverse needs, on of this necessities is the use of structural steels with higher corrosion resistance to marine atmospheres and improved mechanical properties than those that currently exist. Therefore, it is necessary to systematically research both the influence in the corrosion resistant to marine atmospheres of the alloying elements, and others variables such as changes in the manufacturing process of this materials. This work aims to compare the behavior on marine atmospheric corrosion between weathering steels (ASTM A242 and ASTM A588) with ferritic-pearlitic and ferritic-martensitic structures. Wetting and drying cycles were performed. Saline wetting was performed in a salt spray apparatus, according to ASTM B177, while drying was performed in a furnace at 40°C. At the end of each cycles, the corrosion products were removed in accordance to ASTM G1. © 2015, Universidade Federal do Rio de Janeiro. All rights reserved.